(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Wound infections caused by bacteria like Pseudomonas aeruginosa and Klebsiella pneumoniae are a major health risk, especially for immunocompromised individuals. Antibiotic overuse has increased resistance, complicating treatment. Ongoing monitoring and species-specific antibiotic use are vital for effective treatment. Objective(s): To determine the prevalence of micro-organisms responsible for wound infections, identifying the most common pathogens involved, assess the antibiotic susceptibility patterns of these microorganisms to guide effective treatment and prevent the spread of resistant strains. Methodology: In this study, bacterial isolates from wound infections were collected in a clinical setting, and species were identified using common microbiological protocols. Using the disk diffusion method, antibiotic susceptibility and resistance was evaluated by measuring the zone of inhibition. Bacterial species and resistance patterns were compared using statistical techniques such as Chi-Square testing. The therapeutic effect of antibiotics for various isolates was evaluated using descriptive statistics. Results:The study found S.aureus (59%), and E.faecalis (42%) were common in wound infections, after P.aeruginosa(30%), S.pyogens(29%), E.coli(20%) and K.pneumoniae(19%). Meropenem and Imipenem was the most effective antibiotic, while Penicillin and Amikacin showed high resistance. Vancomycin and Ceftriaxone had moderate efficacy with variable susceptibility. The results highlight the importance of species-specific antibiotic selection for treating wound infections. Conclusion(s): The study on the antibiotic susceptibility pattern of bacterial isolates in wound infections reveals important findings regarding the prevalence of pathogens and their resistance to commonly used antibiotics. S. aureus, E. faecalis, and P. aeruginosa are the main causes of wound infections, and their resistance to widely used antibiotics is growing. Penicillin and Amikacin shown great resistance, although Meropenem and Imipenem were the most effective. To improve treatment outcomes and fight resistance, species-specific antibiotic tactics must be tailored.